Activated Single‐Phase Ti4O7 Nanosheets with Efficient Use of Precious Metal for Inspired Oxygen Reduction Reaction. Issue 68 (17th November 2022) - Xu, Fan; Zou, Qing; Xiong, Gangquan; Zhang, Huijuan; Wang, Feipeng; Wang, Yu
Abstract: The oxygen reduction reaction (ORR) is central to modern energy storage and conversion technologies for grids such as fuel cells and electrolyzers, but challenges remain due to the lack of reliable, economic, and durable electrocatalysts. Here, we develop single‐crystal conductive black titanium (Ti4 O7 ) nanosheets (NSs) as a new precious metal carrier based on sacrificial hard templates and ultrasonic‐assisted peeling, and deposit Pt clusters on Ti4 O7 NSs induced by wetness impregnation under the irradiation of visible light (VI; 650 nm). Pt/Ti4 O7 NSs provide Ti 3+, Pt 2+, and Pt 0+ continuous active sites for the ORR multielectron process, achieving synergy among them. The assistance of visible light not only makes a more uniform and smaller distribution of Pt nanoclusters, but also strengthens the charge transfer, thereby constructing a strong metal‐support interaction interface. VI−Pt/Ti4 O7 NSs show superior initial oxidation potential and a mass activity of 1.61 A mg −1 Pt at a E 1/2 =0.91 V, which is nine times higher than that of commercial Pt/C. This work provides an effective strategy for achieving high‐value applications of titanium sub‐oxides and further explores the enhanced interface in metals Tin O2n‐1 by light radiation. Abstract : High‐purity, single‐crystal Ti4 O7 nanosheets with a high specific surface area have been synthesized for the first time. Synergy and a strong metal‐support interaction interface between Pt clusters and Ti4 O7 were constructed with the assistance of visible light irradiation (650 nm). Continuous active sites (Ti 3+, Pt 2+, and Pt 0+ ) for the ORR multielectron process are supplied. The new VI−Pt/Ti4 O7 NSs exhibit excellent ORR activity.